Dimensionality Controlling of Cs3Sb2I9 for Efficient All‐Inorganic Planar Thin Film Solar Cells by HCl‐Assisted Solution Method. Issue 5 (2nd January 2019) - Umar, Farooq; Zhang, Jian; Jin, Zhixin; Muhammad, Ishaq; Yang, Xiaokun; Deng, Hui; Jahangeer, Khan; Hu, Qingsong; Song, Haisheng; Tang, Jiang
Abstract: Since lead halide perovskite suffers from the obstructions of lead and stability, researchers recently pay more attention to the development of lead‐free and stable perovskite absorbers. A typical lead‐free antimony iodide perovskite (AIP) is synthesized through vapor reaction at high temperature for photoactive phase. Herein, hydrochloric acid is developed as an intermediate coordinated additive for Cs3 Sb2 I9 photoactive layered phase using HCl‐assisted solution method. The uniform and highly crystalline Cs3 Sb2 I9 layered film is obtained by antisolvent engineering. Isopropanol antisolvent is more suitable for present system comparing with traditional lead iodide perovskite‐based ones. Physical characterizations manifest the lower trap density, doubled carrier mobility, and improved junction quality from the new developed absorber film and its corresponding devices comparing with its dimer phase. Utilizing TiO2 /AIP/Au all‐inorganic structure, the champion device demonstrates a power conversion efficiency (PCE) of 1.21%, which is the top value for all‐inorganic AIP solar cells. The nonencapsulated device exhibits negligible loss in the PCE under ambient environment with 50% humidity after 60 days storing. The obtained results portray important progress toward the understanding of reliable HCl‐assisted solution method and realization of highly stable AIP solar cells. Abstract : An all‐inorganic antimony halide perovskite layered phase is successfully implemented by solution method with the assistance of hydrochloride (HCl). The HCl additive could change the coordination of cations to guarantee the layer phase at relatively low temperature. The morphology of thin film is further optimized with suitable antisolvent engineering. The all‐inorganic devices obtain a power conversion efficiency of 1.21%.